(3eHGOF GdJShjb (B:s (3Hjf GdfXQjI h GdJWHjb (B/s - (3YRGe, RcQjG CMeOs; (3MShfI, YHO GdHGSWs ((3YeGf(B: s (3OGQ GdeSjQI(B, s, 2011)
(3ebOeI aj GdJShjb , GdHjFI GdJShjbjI h JLRFI GdShb h Sdhc GdeSJgdc h GdeYdheGJ h GdHMhK GdJShjbjI h SjGSGJ h bQGQGJ GdefJLGJ h JWhjQ GdefJLGJ GdLOjOI h JShjb GdNOeGJ , GdJSYjQ h GdJhRjY h GdJQhjL , GdJShjb GdGdcJQhfj h GdJLGQI GdGdcJQhfjI eY hLhO CSFdI ddefGbTI aj fgGjI cd aUds
((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3COGQI GdeHjYGJs; (3GdJShjbs; (3GdJShjb GdEdcJQhfjs